ESTIMATION OF AREA SOWN AND SOWING DATES OF INSEASON RABI CROPS USING SENTINEL-2 TIME SERIES DATA - SANDEEP V.GAIKWAD*, AMOL D. VIBHUTE; KARBHARI V. KALE (The Journal of Research ANGRAU, 2021)
An estimation of the area sown and sowing dates with their frequent updates in crop growing season are crucial for devising the Nation’s food secuirty policies. These areas and dates were estimated in India through a crop simulation model at a 5km X 5km grid across the states. Therefore, a pilot study was conducted crop of sown area estimation, and sowing dates of rabi (post-rainy) crops for 2017-2018 using nine (09) high-resolution Sentinel-2 images. These images were acquired from October 1, 2017, to January 31, 2018 and were used to prepare the Satellite Image Time Series (SITS) dataset. A new methodology was implemented using a time-series vegetation index at 10m spatial resolution Sentinel-2 data to detect rabi crops’ growth in Vaijapur Tehsil of Maharastra. Normalized Difference Vegetation Index (NDVI) was computed from the dataset, and further used for a research study. A composite of 15 images was prepared for analysis of the temporal profile of NDVI. The temporal profile trend starts from the emergence of crops and shows the maximum value at the maturity state of crops. Furthermore, it starts decreasing and shows a minimum threshold value >0.03 at the crop’s harvesting state. Additionally, it was correctly used to differentiate early, normal, and late sown crops in the study area. Furthermore, sown area estimation was carried out by an unsupervised ISODATA (Iterative Self-Organizing Data Analysis) algorithm. The overall accuracy was 88.39 with 0.84 kappa coefficient through the conducted experiment. Sentinel-2 is a suitable data source for sown area estimation and sowing date extraction with acceptable accuracy.